The Mambo Kings play songs of love - Hijuelos, Oscar; Marshall, E. G., 1914-1998. (Beverly Hills, CA : Dove Audio, 1991)
Portrays the story of brothers Cesar and Nestor Castillo, Cuban-born musicians who emigrate to New York City in 1949; form a band named the Mambo Kings and enjoy modest success playing dance halls and nightclubs in New York's Latin neighborhoods; and eventually become recording artists and appear on the I Love Lucy television show with their hero Desi Arnaz.
Abridged.
In container (18 cm.).
Read by E.G. Marshall.
Keywords: Cuban Americans -- Fiction; Musicians -- Fiction; Brothers -- Fiction; New York (N.Y.) -- Fiction